Analysis of the regulatory mechanisms of prognostic immune factors in thyroid cancer - Tian, Yin; Xie, Tao; Sun, Xue (Frontiers in Oncology, 2022)
There are many studies on the prognosis of thyroid cancer (THCA), but its mechanisms are unclear. Now we used bioinformatics to study the prognostic regulatory mechanism of thyroid cancer based on The Cancer Genome Atlas. Using R software, we analyzed the differentially-expressed genes and differential micro ribonucleic acids (miRNAs) between thyroid cancer and normal paraneoplastic tissues. We constructed Least absolute shrinkage and selection operator risk models to obtain nine prognostic immune factors, AKAP12, APOC1, TIMP3, ADAMTS9, ANK2, HTRA3, SYNDIG1, ADAMTS5, and DACT1, by predicting the differential immune prognostic factor miRNA target-binding possibility and correlation analysis by quantitative reverse transcription PCR at the cellular level to explore the regulatory mechanisms of prognostic immune factors in thyroid cancer, as well as to provide a new thyroid cancer treatment.